2019
DOI: 10.1002/path.5216
|View full text |Cite
|
Sign up to set email alerts
|

Activating mutations in the MAP‐kinase pathway define non‐ossifying fibroma of bone

Abstract: Non‐ossifying fibroma (NOF), which occasionally results in pathologic fracture, is considered the most common benign and self‐limiting lesion of the growing skeleton. By DNA sequencing we have identified hotspot KRAS, FGFR1 and NF1 mutations in 48 of 59 patients (81.4%) with NOF, at allele frequencies ranging from 0.04 to 0.61. Our findings define NOF as a genetically driven neoplasm caused in most cases by activated MAP‐kinase signalling. Interestingly, this driving force either diminishes over time or at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
64
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 27 publications
2
64
1
Order By: Relevance
“…Although TRPV4 p.M713V and p.M713I mutations were exclusive to the central variant of giant cell lesion of the jaw, KRAS and FGFR1 also occurred in the peripheral lesions . Overall, whereas in the study by Baumhoer, Kovac, Sperveslage, Amelin et al 81% (48/59) of non‐ossifying fibromas of bone showed either KRAS , FGFR1 or NF1 mutations , in our study 72% (42/58) of sporadic cases of giant cell lesions of the jaws harboured KRAS , FGFR1 or TRPV4 mutations.…”
contrasting
confidence: 57%
See 3 more Smart Citations
“…Although TRPV4 p.M713V and p.M713I mutations were exclusive to the central variant of giant cell lesion of the jaw, KRAS and FGFR1 also occurred in the peripheral lesions . Overall, whereas in the study by Baumhoer, Kovac, Sperveslage, Amelin et al 81% (48/59) of non‐ossifying fibromas of bone showed either KRAS , FGFR1 or NF1 mutations , in our study 72% (42/58) of sporadic cases of giant cell lesions of the jaws harboured KRAS , FGFR1 or TRPV4 mutations.…”
contrasting
confidence: 57%
“…We read with great interest the study by Baumhoer, Kovac, Sperveslage, Amelin et al . In this paper, the authors searched for pathogenic mutations in 59 patients with non‐ossifying fibroma of bone, reporting KRAS mutations in 38 cases, FGFR1 mutations in eight and NF1 mutations in two cases from patients who were known to have neurofibromatosis type 1 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our research group has recently uncovered somatic heterozygous mutations in KRAS , TRPV4 , and FGFR1 genes in central and conventional PGCG of the jaws (Gomes et al, ). In addition, KRAS and FGFR1 mutations have also been reported in non‐ossifying fibroma of the jaws, another giant cell‐rich lesion that shares histopathological features with IA‐PGCG (Baumhoer et al, ). As the pathogenesis of IA‐PGCG is unclear, we hypothesized that the mutations that occur in conventional giant cell granulomas of the jaws could be the underlining genetic events in the lesions associated with dental implants.…”
Section: Introductionmentioning
confidence: 99%